Training des Hör-Seh-Verstehens im Zeitalter der Omnimedialität des Fremdsprachenunterrichts (Überlegungen zur Qualität von Hör-Seh-Textdidaktisierungen) - Chudak, Sebastian (Glottodidactica, 2013)
In our modern media-driven world, the development of audio-visual comprehension is an important goal of teaching and learning foreign languages. Nevertheless, teachers do not work on this goal as effectively as they could, often because the textbooks that they use do not always contain adequate audio-visual content. The didactisation of that content in many cases leaves much to be desired, leaving unexploited potential. The aim of the paper is to review the common task typologies for working with different kinds of films as well as to propose various ways of expanding those typologies, with the ultimate goal to improve learners’ film literacy and intercultural competence.